2011
DOI: 10.1021/ol2029096
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrogenation of 2- and 2,3-Substituted Quinoxalines with Chiral Cationic Ruthenium Diamine Catalysts

Abstract: The enantioselective hydrogenation of 2-alkyl- and 2-aryl-subsituted quinoxalines and 2,3-disubstituted quinoxalines was developed by using the cationic Ru(η(6)-cymene)(monosulfonylated diamine)(BArF) system in high yields with up to 99% ee. The counteranion was found to be critically important for the high enantioselectivity and/or diastereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(33 citation statements)
references
References 48 publications
(16 reference statements)
0
32
0
1
Order By: Relevance
“…Such compounds with chelating nitrogen ligands are effectively used in catalysis, e. g. in water oxidation [23], intramolecular hydroamination of alkynes [24], Diels-Alder reactions [25], asymmetric Michael addition reactions [26], asymmetric hydrogenation [27,28], and transfer hydrogenation [29][30][31], reactions of ketones and imines.…”
Section: Scheme 1 Reaction Conditions In Transfer Hydrogenation Of Amentioning
confidence: 99%
“…Such compounds with chelating nitrogen ligands are effectively used in catalysis, e. g. in water oxidation [23], intramolecular hydroamination of alkynes [24], Diels-Alder reactions [25], asymmetric Michael addition reactions [26], asymmetric hydrogenation [27,28], and transfer hydrogenation [29][30][31], reactions of ketones and imines.…”
Section: Scheme 1 Reaction Conditions In Transfer Hydrogenation Of Amentioning
confidence: 99%
“…Asymmetric hydrogenation of N‐heteroaromatic compounds is considered to be a difficult task due to aromatic resonance stability. Recent developments in asymmetric hydrogenation of N‐heteroaromatic compounds,2 such as 2‐substituted quinolines3–15 and quinoxalines3h, k, 4c, f, 11, 1622 (to give the 1,2,3,4‐tetrahydroquinoline and 1,2,3,4‐tetrahydroquinoxaline derivatives, respectively, in high enantioselectivity), pyridine derivatives,3h, 4g, 23 pyrroles,24 imidazole,25 oxazole,25 and indoles,26 have been remarkable. However, only a few mechanistic studies of the asymmetric hydrogenation of N‐heteroaromatics have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…2-Alkyl-substituted indoles were hydrogenated in very good yields with excellent enantioselectivities (entries 1-11), regardless of either the length of side chain or the position of substituents at the phenyl ring. Notably,e xcellent results were also achieved with 2,3-disubstituted fused ring indolines (entries [12][13][14][15][16]. It was found that the enantiomeric excess increased from 89 to 99 %when increasing the ring size from five-to six-and seven-membered rings.I na ddition, the hydrogenation of 2,3-dimethylindole could be carried out under harsh reaction conditions (entry 17).…”
mentioning
confidence: 99%